2018
DOI: 10.1016/j.diabres.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Improvements of ambient hyperglycemia and glycemic variability are associated with reduction in oxidative stress for patients with type 2 diabetes

Abstract: Improvements in glucose metabolism, including FPG and daily and day-to-day glucose variability, were all correlated with reduced oxidative stress for patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 51 publications
1
36
1
Order By: Relevance
“…® with previous observations that a key outcome of glycemic variability is the overproduction of reactive oxygen species, which, in turn, drives increased endothelial production of inflammatory mediators (35,36). Indeed, in the present study, the increased production of proinflammatory mediators under the variable condition was observed both in vivo and in vitro, and this was associated with more severe influenza.…”
Section: Diabetes and Influenzasupporting
confidence: 91%
“…® with previous observations that a key outcome of glycemic variability is the overproduction of reactive oxygen species, which, in turn, drives increased endothelial production of inflammatory mediators (35,36). Indeed, in the present study, the increased production of proinflammatory mediators under the variable condition was observed both in vivo and in vitro, and this was associated with more severe influenza.…”
Section: Diabetes and Influenzasupporting
confidence: 91%
“…Apart from hyperglycemia itself, glycemic variability is also considered to be related to disturbed hormones and oxidative stress. Studies have reported that glycemic variability was correlated to oxidative stress and erythrocyte membrane stability [24], and improvement in glycemic variability reduced oxidative stress [25]. Based on this evidence, we suspect a potential association between glycemic variability and the development of malignancies through hormonal pathways and oxidative stress in people without diabetes.…”
Section: Introductionmentioning
confidence: 69%
“…This mechanism may be due to the fact that the use of a GLP-1-RA affected oxidative stress and vascular endothelial function characteristics. Another possible reason is that glycemic control was better in patients treated with dulaglutide added on conventional therapy and possibly related to an improvement in glucose variability as reported by some studies (47).…”
Section: Discussionmentioning
confidence: 89%
“…A previous research (47) evidenced that the reduction of FPG and the improvement of glycemic variability is correlated to the reduction of oxidative stress on vascular endothelial.…”
Section: Discussionmentioning
confidence: 90%